INFLUENCE OF FACTORS UNSTABLE ENVIRONMENT ON THE STRATEGY OF INTERACTION BETWEEN STATE AND BUSINESS IN HIGH-TECH SECTORS RUSSIAN ECONOMY - Vyacheslav V. Baranov; Alexander V. Zaytsev; Varvara B. Karpova; Alexander A. Muradov (Статистика и экономика)
The types of the unstable state of the macroeconomic environment affecting the strategy of forming government and business. Applied to high-tech industries studied forms of public-private partnerships. The structure of the organizational problems that arise in the creation and development of effective public-private partnership whose solution minimizes the negative effects of environmental factors.